Effect of Flutter Along with Conventional Chest Physiotherapy on Peak Expiratory Flow Rate among Coronary Artery Bypass Graft Patients - Sabnam Kapadia; Tejas Rameshchandra Chokshi; Mansi Patel (Journal of the Scientific Society, 2023)
Background: Coronary artery bypass graft (CABG) is extensively used to treat patients with heart problems. As it is a major surgery involving the thoracic cavity, lung function may be compromised postoperatively. Pulmonary dysfunction following CABG is inevitable. Chest physiotherapy (CPT) is a treatment to prevent postoperative pulmonary complications. Flutter is a form of positive expiratory pressure device in combination with high-frequency oscillation; it gives independence to patients and is easy to use for airway clearance. Aim: To study the effect of flutter along with conventional CPT on peak expiratory flow rate (PEFR) among CABG patients. Methodology: Twenty-seven CABG patients were selected through simple random sampling and assigned into two groups. Group 1 consisting of 13 patients was treated with conventional CPT, whereas Group 2 consisting of 14 patients was treated with flutter along conventional CPT. Pre- and post-physiotherapy PEFR was noted. Results: The data were analyzed using a paired and unpaired t-test, and there was significant improvement seen in Group 2 as compared to Group 1 (P < 0.001). Conclusion: Flutter device should be amalgamated as a routine practice along with other CPT techniques in CABG patients which can have positive results in airway clearance and thereby improving PEFR.